Fulfillment of the Rights of Persons with Disabilities as Workers in the Formal Sector: A Comparative Study of Indonesia and France - Aldillah, M.; Wasitaatmadja, Fokky Fuad (Veteran Law Review, 2025)
The concept of the state as a protective entity is a fundamental principle in modern legal philosophy, whereby the state acts as an active guarantor of the fulfillment of the fundamental rights of all its citizens without exception. In Indonesia, this commitment is manifested through Law No. 8 of 2016 concerning Persons with Disabilities, which mandates a 2% employment quota for the public sector and 1% for the private sector. However, the reality on the ground shows a significant gap between this legal mandate and the low level of compliance by companies, indicating weak supervision and enforcement of the rules. This study uses a normative juridical method with a regulatory approach and a conceptual approach to analyze the issues raised. The results show that although Indonesian positive law has shifted from a paternalistic paradigm to one based on human rights through Law No. 8 of 2016, its implementation is hampered by the absence of explicit recognition in the constitution and weak enforcement mechanisms. A comparative analysis with France reveals that the “hire or pay” system, supported by special fund management institutions such as Agefiph, offers a more effective and constructive model. Therefore, Indonesia is advised to adopt a similar mechanism with clear sanctions to transform its normative framework into an implementable and sustainable system.